OPINI PEDAGANG KAKI LIMA TERHADAP KEBIJAKAN PENATAAN PEDAGANG KAKI LIMA DI KAWASAN SIMPANG LIMA KOTA SEMARANG - Annissa Yulindha; Hermini .; reni Windayani (Journal of Politic and Government Studies, 2014)
AbstractSemarang Simpang Lima Central Business District which is located in the middle junction of the city which is the center of the city of Semarang. That is why there should be arrangement of street vendors in order to create the atmosphere of the beautiful and neat city. For that the government build shelters for street vendors in order to facilitate a well organized and structured than previously. Public opinion from street vendors community are also required to run properly as expected.The method I use is a qualitative research approach in which a particular social situation reveals the fact description correctly, based on data collection and analysis techniques.The results of this study is mostly from street vendor accept the policy arrangement, because basically they are not disadvantaged, just at the time they were displaced during the construction of the shelter about four months. Now after the opening of the shelter, street vendors get reasonable facilities from the government than ever before.Keywords : Opinion, Regulation, Street vendor, Shelter